Meiji prominent leaders and their perceptions of Western science and technology: a brief analysis - Mansor Majdin, Mohamad Firdaus (Global Academia Network, 2022)
While much research has been undertaken on the Meiji Ishin, nonetheless there is little attention given on what prompted the new Meiji leadership of Japan to introduce reforms in Japan and what model that they should follow. Specifically, this calls for further analysis as to how these Meiji leaders (names include Kido Takayoshi, Ito Hirobumi, Okuma Shigenobu, Okubo Toshimichi, Inoue Kaoru to name but a few), perceived the essentiality of Western science and technology and what benefits that they could bring on Japan as a nation. In doing so, this paper will discuss the views and opinions of some prominent Meiji statesmen and intellectuals about the significance of Western science and technology in Japan following the Meiji Ishin and how they implement them. The study adopts a method of content analysis by scrutinizing archival documents and scholarly works written on a few identified Meiji leaders. In short, the study shows that these prominent Meiji leaders, who had formed the backbone of the Meiji Government in various capacities, held positive views about Western science and technology and they had brilliantly navigated them for Japan’s benefit.